Educational games to support caring and compassion among youth: A design narrative - Siyahhan, Sinem; Ingram-Goble, Adam A.; Barab, Sasha; Solomou, Maria (My University, 2017)
In this paper, the authors argue that video games offer unique and pervasive opportunities for children to develop social dispositions that are necessary to succeed in the 21st century. To this end, they discuss the design of TavCats—a virtual role-playing game that aimed to engage children (ages 9 to 13) in understanding, acting upon, and coming to value being caring and compassionate. The authors' discussion takes the form of a design narrative through which they explain the connections between their theoretical commitments and design decisions. Specifically, they review four design elements they utilized in their design work: identity claims, boundary objects, profession trajectories, and cyclic gameplay. The authors briefly share their observations from a pilot study with children in an afterschool setting to illustrate how their design work might be realized in the world. They conclude their paper with a discussion of the implications of their work for designing educational video games for supporting social dispositions as well as academic learning, and future directions.
Keywords: Design Narrative; Educational Games; Game-Based Learning; Game Design; Serious Games; Social Dispositions; Social Learning; Teaching Caring and Compassion